Influence of the halide and exposed facets on the visible-light photoactivity of bismuth oxyhalides for selective aerobic oxidation of primary amines - Han, Aijuan (ELSEVIER SCIENCE BV, 2019)
10.1016/j.apcatb.2017.07.050